The Supervision of Local Government in Protecting the Forest at Kie Matubu Protected Forest - Muhammad Julham; Tamrin Salim; Muhammad Yasin Majojo; Abdul Azis Ramli (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the supervision of the local government to protect the Kie Matubu Protected Forest Area, Tidore Islands City. This research uses interview method and document study. The data that has been collected was analyzed qualitatively and presented descriptively. The research was conducted at the North Maluku Forestry Service Office. This study found that: in Law No. 23 of 2014, authority was transferred to the provincial government, and based on the results of the study, researchers have obtained answers to existing problems, that the importance of local government supervision in protecting forests due to forest damage caused by irresponsible human actions, such as clearing new land for plantations by burning the forest first, this will result in flooding and landslides when it rains, where the benefits of protected forests should be for raw material providers, soil conservationists, water source providers, and plays an important role as a counterbalance to the environment. Responding to the facts above, the Government's role in this case must be more active in seeking regulations, socialization and the community must maintain the preservation of protected forests and maintain forest ecosystems so that damage does not occur, especially damage to the Kie Matubu Protected Forest area, Tidore Islands City, where in terms of Currently, the government has made various efforts, but there is no public awareness not to use protected forests as production forests or make private plantations without permission from the local government